An application of Kernel estimation method to the demand in two-stage inventory model. Issue 1 (1st January 2017) - Rojas, Fernando
Abstract: This paper proposes an improvement in the form of modeling the demand in models of stochastic inventories. For these purposes, it is proposed to occupy the Kernel estimation method to the demand per unit of time and demand during the lead time to generate input scenarios for a stochastic programming in two-stage, in a model of continuous review with shortage. An application of this methodology considers the obtaining of this scenarios from the modeling of actual data of demand of inputs of food service. The possibility of working directly with the densities and accumulated probabilities of demand in an empirical and more realistic way with regard to the data available, improve the task for the decision makers of the operations management.